Leukemoid Reaction in an Elderly Patient with Aortic Valve Infective Endocarditis and Pancreatic Adenocarcinoma - E. V. Reznik; M. A. Batov; T. V. Aparina; O. V. Kim; M. Kh. Shurdumova; L. M. Mikhaleva; A. P. Smirnov; G. N. Golukhov (SINAPS LLC, 2024)
Leukemoid reaction (LR) associated with solid tumors has been documented for many decades. LR is often associated with an unfavorable prognosis and aggressive course of the disease. However, the differential diagnosis of LR is of significant difficulty when a patient has several potential etiological factors, each of them individually may cause LR or, on the contrary, lead to a systemic reaction of the body within a single pathogenetic chain.We present a clinical observation of an elderly patient admitted to the intensive care unit due to the first-time encountered weakness in the right extremities. Clinical and instrumental examination revealed an acute cerebral ischemia with leukocytosis increase up to 60.000 cells/μL with leukocyte formula left shift and subsequent patient decompensation with lethal outcome, despite the intensive treatment.Autopsy revealed a low-differentiated adenocarcinoma of the pancreatic tail with multiple metastatic lesions in regional lymph nodes and liver, as well as a competing disease - acute infective endocarditis of the aortic valve, which was the cause of sepsis development with septicemia type and thromboembolism both in the great circulation circle with the presence of ischemic cerebral infarction, spleen infarcts, and in the small circle with the development of thromboembolism in the right segmental branches of the pulmonary artery. Given the advanced stage of pancreatic cancer and lack of direct evidence of sepsis at primary diagnosis, paraneoplastic nature of LR is more likely, but infective endocarditis and concomitant pathology also may have contributed to the development of LR.